Investigating slow shock in low-impedance materials using a direct impact Hopkinson bar setup - Jakkula Puneeth; Ganzenmüller Georg; Beisel Samuel; Hiermaier Stefan (EPJ Web of Conferences, 2021)
This work implements a direct impact Hopkinson bar, suitable for investigating the evolution of dynamic force equilibrium in low-impedance materials. Polycarbonate as the bar material favours for a long pulse duration of 2.6 ms for an overall length of only 5 m, allowing to compress large specimens to high strains. This setup is applied to polyurethane foams with different densities ranging from 80 - 240 kg/m3. Dynamic compression tests are performed at strain rates of 0.0017, 0.5 and 500 /s on the foams at room temperature. Depending on density, they show a saturation in increase of yield strength at strain rates of 500 /s, or even show a negative strain rate sensitivity for the lowest density. This behaviour is explained by comparing the dynamic force equilibrium to a phenomenon similar to shock in solid materials: For low densities and high rates of strain, homogeneous compression is replaced by a localized collapse front with a jump in stress across the front. Digital image correlation is performed to analyse elastic and plastic compaction waves by means of Lagrange diagrams.